Molecular Biology - Channarayappa (University Press, 2015)
The study of molecular biology has widespread applications covering genetic research, drug delivery systems, stem cell therapy and cancer treatment. The functioning of biological systems is based on the flow of genetic information from the nucleotides of the DNA to the RNA leading to the production of various cellular proteins. Thus, control is exercised only by modifying the various stages of protein synthesis. Hence, the ideal approach to the study of the subject is in understanding the genetic processes that are reflected as changes in protein reactions. This book is a comprehensive overview of the subject and is written in a clear and simple language. It also incorporates several student-friendly features. There are numerous illustrations and tables that will enable the readers to grasp the concepts easily. Each chapter begins with Learning Objectives and includes Key Points and Self-assessment Questions. The Further Reading section guides the students towards advanced discussion of the topics. It is hoped that the book will be a valuable textbook to students of biotechnology, genetics and other courses which have molecular biology as a component.